Palladium-catalyzed coupling of ammonia and hydroxide with aryl halides: the direct synthesis of primary anilines and phenols. - Willis, M (2007)
(Chemical Equation Presented) Back to basics: Ligand design has allowed two longstanding limitations of Pd-catalyzed C-N and C-O coupling reactions to be overcome. The use of specific sterically demanding electron-rich phosphine ligands makes it possible for ammonia and potassium hydroxide to act as coupling partners in palladium-catalyzed coupling with aryl halides. © 2007 Wiley-VCH Verlag GmbH and. Co. KGaA.